Adverse Responses following Exposure to Subtoxic Concentrations of Zinc Oxide and Nickle Oxide Nanoparticles in the Raw 264.7 Cells - Nasser B. Alsaleh; Mohammed A. Assiri; Anas M. Aljarbou; Mohammed M. Almutairi; Homood M. As Sobeai; Ali A. Alshamrani; Sultan Almudimeegh (Toxics, 2023)
The incorporation of engineered nanomaterials (ENMs) in biomedical and consumer products has been growing, leading to increased human exposure. Previous research was largely focused on studying direct ENM toxicity in unrealistic high-exposure settings. This could result in overlooking potential adverse responses at low and subtoxic exposure levels. This study investigated adverse cellular outcomes to subtoxic concentrations of zinc oxide (ZnONPs) or nickel oxide (NiONPs) nanoparticles in the Raw 264.7 cells, a macrophage-like cell model. Exposure to both nanoparticles resulted in a concentration-dependent reduction of cell viability. A subtoxic concentration of 6.25 µg/mL (i.e., no observed adverse effect level) was used in subsequent experiments. Exposure to both nanoparticles at subtoxic levels induced reactive oxygen species generation. Cellular internalization data demonstrated significant uptake of NiONPs, while there was minimal uptake of ZnONPs, suggesting a membrane-driven interaction. Although subtoxic exposure to both nanoparticles was not associated with cell activation (based on the expression of MHC-II and CD86 surface markers), it resulted in the modulation of the lipopolysaccharide-induced inflammatory response (TNFα and IL6), and cells exposed to ZnONPs had reduced cell phagocytic capacity. Furthermore, subtoxic exposure to the nanoparticles distinctly altered the levels of several cellular metabolites involved in cell bioenergetics. These findings suggest that exposure to ENMs at subtoxic levels may not be devoid of adverse health outcomes. This emphasizes the importance of establishing sensitive endpoints of exposure and toxicity beyond conventional toxicological testing.